2022
DOI: 10.1021/acs.macromol.2c01027
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl-Induced Crosslinking of Polymer Membranes for Highly Selective CO2/CH4 Separation with Enhanced Stability

Abstract: Chemical crosslinking is the most commonly used solution to address the issue of poor structure stability and low plasticization resistance of polymer membranes for gas separation. However, the general crosslinking route requires the introduction of reactive groups into the polymer chain and is very likely to weaken the separation performance of membranes. Here, we report a new and nondestructive benzyl-induced crosslinking strategy. Owing to the high reactivity and wide existence in most polymers, the benzyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…36 In addition, the stability of thermal oxidation crosslinking is greatly improved with the use of reactivity of a benzyl moieties and thermal crosslinking can be conducted at a relatively low temperature of 250 1C due to the high reactivity of the -CH 3 group. 37 Benzyl polyimide membranes were synthesized via a polycondensation reaction of (4,4 0 -hexafluoroisopropylidene) diphthalic anhydride (6FDA) and para-phenylenediamine. This crosslinked membrane has a CO 2 /CH 4 selectivity of more than 70 and a plasticization resistance that is three times higher than non-crosslinked membranes in CO 2 , allowing it to withstand up to 42 bar without sustaining damage.…”
Section: Thermally Induced Crosslinkingmentioning
confidence: 99%
“…36 In addition, the stability of thermal oxidation crosslinking is greatly improved with the use of reactivity of a benzyl moieties and thermal crosslinking can be conducted at a relatively low temperature of 250 1C due to the high reactivity of the -CH 3 group. 37 Benzyl polyimide membranes were synthesized via a polycondensation reaction of (4,4 0 -hexafluoroisopropylidene) diphthalic anhydride (6FDA) and para-phenylenediamine. This crosslinked membrane has a CO 2 /CH 4 selectivity of more than 70 and a plasticization resistance that is three times higher than non-crosslinked membranes in CO 2 , allowing it to withstand up to 42 bar without sustaining damage.…”
Section: Thermally Induced Crosslinkingmentioning
confidence: 99%
“…Because of its inherent interchain interaction, it shows high membrane density (1.27 g/mL) and denser chain packing than other glassy polymers. − To further increase chain rigidity and decrease free volumes, Lin’s group reported the use of H 3 PO 4 and terephthaloyl chloride to cross-link PBI to improve its size-sieving ability, thereby increasing the H 2 /CO 2 selectivity by almost 100%. , In addition, H 2 /CO 2 selectivity of polyimides could be improved via diamine cross-linking to manipulate chain rigidity and chain-packing efficiency. Chung’s group reported that a polyimide (6FDA-durene) membrane could be cross-linked by various amines such as ethylenediamine (EDA), diethylenetriamine (DETA), diaminobutane (DAB) dendrimers, and other diamines, and H 2 /CO 2 selectivity increased by more than 260%. − This approach involves the reaction of the imide ring of polyimide with a cross-linker molecule to produce a polymer network structure. ,− Their results showed that chemical cross-linking of polyimide membranes remains one of the most promising methods for improving H 2 enrichment. However, these methods mentioned above usually face several challenges: (1) only a few polymers with rigid structure that can be directly used to separate H 2 and CO 2 ; (2) the serious loss of permeability due to the denser chain packing after modification; (3) the destruction of the main chain of the polyimide caused by excessive reaction and the decrease of molecular weight of the polymer after cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic liquid-embedded PI films could withstand a low folding radius, but the affordable amount of folding was only 4, which was far away from 200,000 . The PI films crosslinked by a covalent or hydrogen bond network exhibited good folding resistance under a folding radius about 2–3 mm, but the crosslinked films with brittleness cannot afford the increased strain with the decrease in folding radius. ,,− In addition, the exponential impact of folding radius on the tested folding reliability of PI films was further confirmed in this work. Thus, there were still difficulties in preparing large curvature folding-resistant PI films, and a novel strategy was an urgent need for enhancing the folding resistance of PI films under a large curvature.…”
Section: Introductionmentioning
confidence: 99%